New species of the snakefly genus Mongoloraphidia (Raphidioptera: Raphidiidae) from China - Liu, Xingyue; Lyu, Yanan; Aspöck, Horst; Aspöck, Ulrike (Zootaxa, 2018)
Two new snakefly species of the family Raphidiidae are described from China: Mongoloraphidia lini sp. nov. and Mongoloraphidia triangulata sp. nov. Biogeographical considerations on secondary refugial centers of the large Sino-Tibetan primary center are presented.